2015
DOI: 10.1002/ajmg.b.32339
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic and gene wide effects in YWHA and aromatic amino hydroxylase genes across ADHD and other common neuropsychiatric disorders: Association with YWHAE

Abstract: Monoamines critically modulate neurophysiological functions affected in several neuropsychiatric disorders. We therefore examined genes encoding key enzymes of catecholamine and serotonin biosynthesis (tyrosine and tryptophan hydroxylases—TH and TPH1/2) as well as their regulatory 14‐3‐3 proteins (encoded by YWHA‐genes). Previous studies have focused mainly on the individual genes, but no analysis spanning this regulatory network has been reported. We explored interactions between these genes in Norwegian pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…These data suggest that complex I, the first complex of the OXPHOS, which contributes about 40% of the proton motive force that drives adenosine 5′‐triphosphate (ATP) synthesis by ATP synthase (complex V) and is a main site for ROS production, is a vulnerable module in situations requiring cellular adaptation. The expression of PSEN1, DAB1, YWHAE and JUN, all associated with synaptic plasticity and with cognitive function also showed inverse time‐dependent dynamics. Two additional genes showed similar inverse trajectory in MTR treated rats, PACS1 and AP2B1.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These data suggest that complex I, the first complex of the OXPHOS, which contributes about 40% of the proton motive force that drives adenosine 5′‐triphosphate (ATP) synthesis by ATP synthase (complex V) and is a main site for ROS production, is a vulnerable module in situations requiring cellular adaptation. The expression of PSEN1, DAB1, YWHAE and JUN, all associated with synaptic plasticity and with cognitive function also showed inverse time‐dependent dynamics. Two additional genes showed similar inverse trajectory in MTR treated rats, PACS1 and AP2B1.…”
Section: Discussionmentioning
confidence: 94%
“…Out of the 30 qRT‐PCR validated genes, 3 showed a significant correlation between expression and behavioural responses. A significant negative correlation was observed between the percentage of errors in the T‐maze test and the expression levels of the following genes in the PFC: NDUFV2, which encodes for mitochondrial Complex I subunit ( R = −0.781, P < .01) (Figure A); Ywhae, encoding for 14‐3‐3 ε protein which is an adapter protein implicated in the regulation of a large spectrum of both general and specialized signalling pathways and has been implicated in schizophrenia and Alzheimer disease ( R = −0.703, P < .01) (Figure B); DAB1, which is involved in directing neuronal positioning in the developing brain ( R = −0.582, P < .05) (Figure C). In addition, a significant negative correlation was observed between the anxiety index and PFC NDUFV2 gene expression levels ( R = −0.580, P < .05) (Figure D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin dysregulation has also been proposed to play a role in autism [99]. Variants in TPH2 have also been associated with major depression, bipolar disorder, suicidal behavior, personality disorder, and ADHD [100]. However, in large genome wide association studies, common variants in TH, TPH1, or TPH2 have not shown convincing associations with any known human phenotypes tested so far.…”
Section: Tph1 and Tph2 In Human Physiology Disease And Mouse Modelsmentioning
confidence: 99%
“…However, in large genome wide association studies, common variants in TH, TPH1, or TPH2 have not shown convincing associations with any known human phenotypes tested so far. A recent comprehensive analysis of variants in TH, TPH1, and TPH2, as well as the 14-3-3 genes (YWHAs), across several psychiatric disorders has shown modest effects for the hydroxylase genes, but significant association of 14-3-3 epsilon (YWHAE) with schizophrenia [100].…”
Section: Tph1 and Tph2 In Human Physiology Disease And Mouse Modelsmentioning
confidence: 99%